KONSTRUKSI IDENTITAS KEACEHAN PASCA KONFLIK DAN TSUNAMI Relasi Masyarakat, Negara, dan Pasar dalam Kebangkitan Lokal di Banda Aceh - , IBNU MUJIB ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study departs from an empirical as well academic anxiety explains why the Acehnese identity is not constructed by local Acehnese itself, but it tends to be constructed by global forces. The Academic problem that arises then is anyone in a relationship of actors and how Acehnese identity formation processes take place? Correspondingly, the identity negotiation process as what was built so that the ideas of resurrection into Aceh mainstream issues at the end of the on going post-conflict period and the tsunami in Aceh. This study used qualitative methods tied to the describtive-interpretatif approach, where one of them is marked with a perspective that is built based on the interpretations and experiences of the subject. In addition to methods of participant observation and in-depth interviews, focus group discussion method was also used for fishing outside opinion or idea that the data can not be delivered in an individual interview. Theoretically, this dissertation uses the theory of social construction which was introduced by Berger and Luckmann, which that identity is constructed by social reality. As usual a social reality, need to support the theoretical support of the actor as introduced in the Schutzâs social phenomenological construction paradigm which describes actors as subjects who participated in identity formation. In that discussion, this dissertation has demonstrated that the fact of Acehnese identity formation is not only built by the people of Aceh alone, but also it has been constructed by people / individuals, institutions, or agencies outside of Aceh, both the mission and its interest as an state, market, and society agency. No wonder if the contestation of diverse actors is happening in determining the future of the ânew Acehâ, Aceh better, Aceh raisin and dignified vision. Therefore, identity formation was constructed by society, state, and market that has been integrated participatively through various forms of dialogue and long negotiation. Through the negotiation process are built, the reactualization of public space, as well as the institutionalization of local wisdom in the form of the qanun, has created a culture of openness and political democratization that is now being felt by the Aceh societies, both in the cultural independence and politic. Keyword: Acehnese, identity construction and its formation, actors, public spaces, negotiations, globalization, and Aceh revival